Potensi Madu sebagai Terapi Topikal Otitis Eksterna - Yunis Sucipta Ibnu (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2019)
Otitis externa (OE) is an external microbial Meatus acousticus (MAE) infection due to damage to the normal MAE serumen skin coat that protects and maintains MAE moisture and temperature. Living in the warm and humid tropics, a decrease in skin pH due to activity in the water including swimming, and excess cerumen cleaning are predisposing factors for OE. The use of antibiotics locally concentrated in OE can not only attack pathogenic microbes but also have an impact on normal flora so that it has the potential to cause resistant microbes. Honey has anti-bacterial properties without the risk of resistance and has even been shown to modulate immunity and inflammation. Various invivo and invitro studies prove that honey has broad spectrum anti-bacterial activity. Honey is proven invitro to modulate immunity by affecting the release of various inflammatory cytokines. This shows that honey has the potential for OE therapy. This article aims to discuss the potential of honey as a topical OE therapy in the hope that it can be an alternative choice of therapy in the management of OE in humans that is safe, effective, and efficient.